Mechanism of action of Bioactive Endodontic Materials - Estrela, Carlos; Cintra, Luciano Tavares Angelo [UNESP]; Duarte, Marco Antônio Hungaro; Rossi-Fedele, Giampiero; Gavini, Giulio; Sousa-Neto, Manoel Damião (FapUNIFESP (SciELO), 2023)
A continuous search for bioactive materials capable of supporting the replacement of damaged pulp tissue, with effective sealing potential and biocompatibility, has represented the attention of studies over the last decades. This study involves a narrative review of the literature developed by searching representative research in PUBMED/MEDLINE and searches in textbooks associated with the mechanism of action of bioactive materials (calcium hydroxide, mineral trioxide aggregate (MTA), and calcium silicate cements). The reflective analysis of the particularities of the chemical elements of these materials, considering the tissue and antibacterial mechanism of action, allows a better understanding of the characteristics and similarities in their tissue responses. Calcium hydroxide paste remains the antibacterial substance of choice as intracanal dressing for the treatment of root canal system infections. Calcium silicate cements, including MTA, show a favorable biological response with the stimulation of mineralized tissue deposition in sealed areas when in contact with connective tissue. This is due to the similarity between the chemical elements, especially ionic dissociation, the potential stimulation of enzymes in tissues, and the contribution towards an alkaline environment due to the pH of these materials. The behavior of bioactive materials, especially MTA and the new calcium silicate cements in the biological sealing activity, has been shown to be effective. Contemporary endodontics has access to bioactive materials with similar properties, which can stimulate a biological seal in lateral and furcation root perforations, root-end fillings and root fillings, pulp capping, pulpotomy, apexification, and regenerative endodontic procedures, in addition to other clinical conditions.